DISHARMONISASI RUMAH TANGGA PADA PASANGAN MUDA AKIBAT JUDI ONLINE: PERSPEKTIF HUKUM KELUARGA ISLAM DI KELURAHAN TANJUNG AMAN KABUPATEN LAMPUNG UTARA - Muhammad Eko Priyono; Nurnazli; Dharmayani (USRAH: Jurnal Hukum Keluarga Islam, 2026)
Advances in digital technology have increased access to online gambling, which has impacted family life, particularly among young couples. This study aims to analyze the forms of marital discord resulting from online gambling and examine them from the perspective of Islamic family law. The research method employed is qualitative, utilizing descriptive-analytical and normative-empirical approaches. Data were collected through interviews, observations, and documentation involving three young couples, religious leaders, and community leaders in Tanjung Aman Village, Kotabumi Selatan Subdistrict, North Lampung Regency. The results of the study indicate that online gambling leads to deteriorating communication, loss of trust, neglect of responsibilities, recurring conflicts, and reduced attention toward one’s partner. Its impacts include economic instability, neglect of family obligations, and a decline in domestic harmony. From the perspective of Islamic family law, online gambling constitutes maysir, which entails mafsadah, contradicts the maqāṣid al-usrah, and can be categorized as nusyuz and syiqaq. This study contributes to the development of Islamic family law research regarding the protection of family resilience from the impacts of online gambling.